Therapeutic Approaches To Raktarsha: An Evidence-Based Ayurvedic Review - Kuchanur, Sarojani; Pathak, Avnish; Goyal, Parveen (Journal of Neonatal Surgery, 2025)
Background: Raktarsha (bleeding piles) is a common anorectal disorder characterized by bleeding during defecation, often accompanied by pain and prolapse. In Ayurveda, it is classified under Arsha and is primarily attributed to the vitiation of Pitta and Rakta. Despite being a frequently encountered clinical condition, its comprehensive management requires a detailed understanding of both traditional and modern therapeutic approaches. Aim To review Ayurvedic therapeutic approaches for Raktarsha and evaluate their efficacy with modern evidence. Objectives To study Nidana and Samprapti of Raktarsha. To review Ayurvedic treatments including Bheshaja, Kshara, Agni, and Shastra Karma. To correlate Ayurvedic and modern concepts. To assess evidence-based studies on Ayurvedic management. To suggest integrative treatment protocols. Materials and Methods: A critical review of classical Ayurvedic texts, published research articles, and modern medical literature was conducted. Databases such as PubMed, Google Scholar, and AYUSH Research Portal were searched using relevant keywords. Studies focusing on Raktarsha etiology, pathogenesis, clinical features, and therapeutic approaches were included. Results: Ayurvedic management emphasizes Shamana (palliative) and Shodhana (purificatory) therapies including Kshara Karma, Agnikarma, and Bhedana Karma alongside herbal formulations like Arshoghni Vati, Abhayarishta, and Triphala. Dietary modifications and lifestyle corrections are integral. Modern treatments include oral venotonic agents, rubber band ligation, sclerotherapy, and surgical hemorrhoidectomy. Evidence suggests that integrative approaches improve symptomatic relief and quality of life. Conclusion: An integrative approach combining evidence-based Ayurvedic therapies with modern techniques offers effective management of Raktarsha, addressing both symptomatic relief and underlying pathology